Corporate criminal responsibility in environmental crimes regarding air pollution due to forest fires: an analysis from an international legal perspective - Ahmad Sepei; Rani Yuwafi; Sofa Laela (Institute Of computer Science (IOCS), 2023)
Indonesia is a developing country and one of its natural resources is the forest, which is one of the determining factors for the survival and welfare of its people. Forest fires are cases that often occur and cause many negative impacts in Indonesia, one of the consequences is air pollution which is getting out of control so that its effects spread to neighboring countries. Most of the causes of giftedness occur as a result of activities carried out by a corporation that is irresponsible and neglectful of the rules and principles of the obligation to always maintain the environmental integrity of the country that is its parent country. The author's goal in conducting this research is to analyze international legal issues with the title Corporate Criminal Responsibility in Environmental Crimes About Air Pollution Due to Forest Fires: Analysis from an International Legal Perspective. This research is descriptive-analytical by examining systematically the accurate facts that exist using normative legal research methods